Efeitos das mutações E484A, E484K e E484Q na proteína Spike do SARSCoV-2: Um estudo in silico - JÉSSICA DE MORAES CARRETONE (2022)
COVID-19, caused by the SARS-CoV-2 virus, became a pandemic in March 2020 and since then has caused numerous damages, both material, and lives. Like all RNA viruses, it has a high capacity for mutation, mainly in the Spike protein. The objective is to analyze the effects of mutations E484A, E484K and E484Q, in comparison with the native structure, through Molecular Dynamics. The RMSD and RMSF data showed that the E484K variant had the greatest variation between all variants and the native one. The E484A and E484Q variants showed similar behavior to the native one. The loop region that binds to the ACE-2 receptor showed lower values of RMSD and RMSF in all variants and the native one.